2015
DOI: 10.1016/j.dnarep.2015.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, and characterization of nucleosomes containing site-specific DNA damage

Abstract: How DNA damaged is formed, recognized, and repaired in chromatin is an area of intense study. To better understand the structure activity relationships of damaged chromatin, mono and dinucleosomes containing site-specific damage have been prepared and studied. This review will focus on the design, synthesis, and characterization of model systems of damaged chromatin for structural, physical, and enzymatic studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 83 publications
(130 reference statements)
0
12
0
Order By: Relevance
“…see ]. These studies helped form the basis for our understanding of the “efficiency” of DNA excision repair [both nucleotide excision repair (NER) and base excision repair (BER)] in chromatin . Early on, it was clear that some classes of DNA lesions ( e.g .…”
Section: Uv Damage To Dna In Chromatin (Pre‐genomic Era)mentioning
confidence: 99%
See 1 more Smart Citation
“…see ]. These studies helped form the basis for our understanding of the “efficiency” of DNA excision repair [both nucleotide excision repair (NER) and base excision repair (BER)] in chromatin . Early on, it was clear that some classes of DNA lesions ( e.g .…”
Section: Uv Damage To Dna In Chromatin (Pre‐genomic Era)mentioning
confidence: 99%
“…Although these studies are beyond the scope of the present review, the reader is referred to recent reviews that cover these topics [ e.g . ].…”
Section: Uv Damage To Dna In Chromatin (Pre‐genomic Era)mentioning
confidence: 99%
“…Most of DNA deformations take place in the SHL ± 1.5 zone. It has an 298 increased binding of DNA proteins and it is most susceptible to DNA damage [38].…”
Section: Patterns In Yeastmentioning
confidence: 99%
“…In addition to the 34 sequence composition there are other factors in vivo such as post-translational 35 modifications (PTM) of histone tails, transcription factor binding and remodeling 36 complexes that influence positioning of nucleosomes and in turn tune chromatin 37 accessibility and gene expression [5,18]. 38 It was shown that nucleosome remodeling takes place in response to stress and alters 39 a gene expression. A single cell study performed on nucleosomes in yeast under glucose 40 rich (PHO5 gene is silenced) and glucose starvation (PHO5 gene is expressed) 41 conditions revealed that under starvation yeast cells lose nucleosomes in the PHO5 42 promoter [2].…”
Section: Introductionmentioning
confidence: 99%
“…23 Herein, the inuence of the vicinal presence of an abasic site near an 8-oxodG lesion and Tg:G mismatch was evaluated by estimating the cleavage efficiency of the repair specic enzymes hOGG1 and hNTH1, respectively, in a two lesion, as well as a three lesion, oligonucleotide model. Our studies show that the abasic site presents a signicant hurdle in the efficient repair of the Tg:G mismatch and 8-oxodG lesion by introducing conformational destabilization in the DNA that prevents proper interaction of the lesion specic enzymes with the lesions.…”
Section: 22mentioning
confidence: 99%